Solidarity in biomedicine and beyond / Barbara Prainsack, Alena Buyx. - Prainsack, Barbara; Buyx, Alena (Cambridge bioethics and law., 2017)
In times of global economic and political crises, the notion of solidarity is gaining new currency. This book argues that a solidarity-based perspective can help us to find new ways to address pressing problems. Exemplified by three case studies from the field of biomedicine: databases for health and disease research, personalised healthcare, and organ donation, it explores how solidarity can make a difference in how we frame problems, and in the policy solutions that we can offer.